2005
DOI: 10.1523/jneurosci.1125-05.2005
|View full text |Cite
|
Sign up to set email alerts
|

The Generation of a 17 kDa Neurotoxic Fragment: An Alternative Mechanism by which Tau Mediates β-Amyloid-Induced Neurodegeneration

Abstract: Recently, we have shown that the microtubule-associated protein tau is essential for ␤-amyloid (A␤)-induced neurotoxicity in hippocampal neurons. However, the mechanisms by which tau mediates A␤-induced neurite degeneration remain poorly understood. In the present study, we analyzed whether tau cleavage played a role in these events. Our results showed that pre-aggregated A␤ induced the generation of a 17 kDa tau fragment in cultured hippocampal neurons. The generation of this fragment was preceded by the acti… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

16
255
2

Year Published

2008
2008
2018
2018

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 239 publications
(273 citation statements)
references
References 63 publications
16
255
2
Order By: Relevance
“…Both tau fragmentation and neurotoxic effects of A␤ could be diminished by calpain-1 inhibition. 186 To date, however, no direct proof for the suggested neurotoxicity of the 17-kD tau fragment has been provided.…”
Section: Tau Clearancementioning
confidence: 99%
See 1 more Smart Citation
“…Both tau fragmentation and neurotoxic effects of A␤ could be diminished by calpain-1 inhibition. 186 To date, however, no direct proof for the suggested neurotoxicity of the 17-kD tau fragment has been provided.…”
Section: Tau Clearancementioning
confidence: 99%
“…Interest in tau is growing, especially after discovery of several tau mutations in FTDP-17 and in light of recent reports that suggested tau as a downstream mediator of a␤-conferred toxicity. 186,226 Counteracting tau neurotoxicity will therefore be a promising strategy, and even more so when combined with anti-A␤ directed approaches.…”
Section: Perspectivesmentioning
confidence: 99%
“…Tissue-derived endogenous formaldehyde even at such a low concentration can induce pain behavior [7,22] . Previous studies have demonstrated that formaldehyde exposure at 0.01-0.1% (~3.3 to ~33 mmol/L) induces mis-folding and aggregation of tau protein in hippocampal neurons [9] , which is essential to beta-amyloidinduced neurodegeneration [23] . Cognitive impairments in senile dementia have also been associated with elevated endogenous formaldehyde concentration [10] .…”
Section: Discussionmentioning
confidence: 99%
“…AβOs, which are increasingly considered to act as proximal neurotoxins in AD, interact with glutamate receptors at the dendritic membrane, induce abnormal calcium influx and oxidative stress, block long-term potentiation (LTP), and facilitate long-term depression, ultimately leading to synapse failure [3,4] . It has recently been suggested that the deposition of Aβ might trigger a series of cellular events that lead to posttranslational changes in Tau followed by neurite degeneration [2,5] . Furthermore, experiments in both cultured rodent hippocampal neurons and transgenic mice demonstrate that Tau is intrinsically involved in Aβ-mediated neuronal dysfunction and cell death [6,7] .…”
Section: Introductionmentioning
confidence: 99%
“…Taken together, the data suggest that there is an intrinsic relationship between Aβ and Tau dysfunction. It has been shown that the deposition of Aβ induced the activation of calpain-1 and caspase-3 proteases [2,5,8] . These proteases cleave Tau proteins at specific sites, generating toxic Tau fragments or enhancing the aggregation properties of Tau protein [2,5,9] .…”
Section: Introductionmentioning
confidence: 99%